2018
DOI: 10.5327/z2176-947820180169
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da condutividade hidráulica em dois usos do solo na região central do Brasil

Abstract: RESUMOUma avaliação das condutividades hidráulicas em solos com tipos distintos de uso e ocupação -cultivo agrícola e cerrado nativo -foi realizada com a finalidade de verificar a interferência das intensas atividades agrícolas no processo de infiltração da água no solo e, consequentemente, recarga de aquíferos. Para determinação da condutividade hidráulica saturada em campo foram empregados permeâmetro Guelph e infiltrômetro de anel duplo. Os ensaios foram realizados em extensa área que abrange cinco estados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…We have also found that in areas with more intense cultivation, as in the municipalities of Quixeré and Limoeiro do Norte, hydraulic conductivity values were lower than in non-cultivated soils, making infiltration and aquifer recharge more difficult. These results are aligned with the findings of Soto and Kiang (2018).…”
Section: Slope and Surface Runoff Of Soilssupporting
confidence: 90%
“…We have also found that in areas with more intense cultivation, as in the municipalities of Quixeré and Limoeiro do Norte, hydraulic conductivity values were lower than in non-cultivated soils, making infiltration and aquifer recharge more difficult. These results are aligned with the findings of Soto and Kiang (2018).…”
Section: Slope and Surface Runoff Of Soilssupporting
confidence: 90%
“…This method does not have many difficulties in its execution and results in more homogeneous values. Unfortunatelly, the concentric ring method offers overestimated values of k sat , due to the imposed hydraulic head 30 .…”
Section: Methodsmentioning
confidence: 99%
“…The proposed apparatus is also intended for the study of erosion processes, therefore requiring runoff generation. However, the saturated hydraulic conductivity of typical soils in the region is relatively high [46][47][48]. Therefore, runoff is generated only during high intensity events.…”
Section: Methodsmentioning
confidence: 99%